2016
DOI: 10.1021/jacs.6b04155
|View full text |Cite
|
Sign up to set email alerts
|

Organometallic Complex Formed by an Unconventional Radical S-Adenosylmethionine Enzyme

Abstract: Pyrococcus horikoshii Dph2 (PhDph2) is an unusual radical SAM enzyme involved in the first step of diphthamide biosynthesis. It catalyzes the reaction by cleaving S-adenosylmethionine (SAM) to generate a 3-amino-3-carboxy propyl (ACP) radical. To probe the reaction mechanism, we synthesized a SAM analog (SAMCA), in which the ACP group of SAM is replaced with a 3-carboxyallyl group. SAMCA is cleaved by PhDph2, yielding a paramagnetic (S = 1/2) species, which is assigned to a complex formed between the reaction … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
14
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 20 publications
2
14
0
Order By: Relevance
“…These two components were designated conformer 1 and conformer 2, respectively. Similar spectra reported in previous studies of the Fe-S cluster concluded that the spectra are derived from a mixture of two different structures of the [4Fe-4S] cluster 30 , or from an identical form of the [4Fe-4S] cluster but in two different reduction states 31 . Accordingly, the Supplementary Fig.…”
Section: Resultssupporting
confidence: 84%
“…These two components were designated conformer 1 and conformer 2, respectively. Similar spectra reported in previous studies of the Fe-S cluster concluded that the spectra are derived from a mixture of two different structures of the [4Fe-4S] cluster 30 , or from an identical form of the [4Fe-4S] cluster but in two different reduction states 31 . Accordingly, the Supplementary Fig.…”
Section: Resultssupporting
confidence: 84%
“…Our studies here thus have revealed that the [4Fe-4S] cluster in a radical SAM enzyme can be tuned to cleave any one of the three bonds to the sulfonium sulfur of SAM or analogues. Together with recent studies on PFL-AE and Ph Dph2, 17,29 our study provides compelling evidence for the versatility of these [4Fe-4S] clusters.…”
supporting
confidence: 82%
“…33b). 154 Originally, SAM CA was used as a potential means of trapping the ACP radical as a stable allylic radical. However, the expected radical was not observed, and instead, the reaction of PhDph2 with SAM CA produced sulfinic acids 83 and 84 as a result of quenching of the expected allylic radical by sodium dithionite.…”
Section: Noncanonical Radical Sam Enzymesmentioning
confidence: 99%